Full P4 to P3− Reduction with a Redox-Active Metal Crown Complex - Maurer, Johannes; Schmidt, Marcel; Nägel, Michael; Färber, Christian; Langer, Jens; Harder, Sjoerd (Angewandte Chemie International Edition, 2025)
Traditional bulk syntheses of phosphorus compounds start with P4 to PCl3 oxidation but more sustainable methods cleave P─P bonds reductively. This generally results in larger polyphosphide Zintl anions: Pmnˉ. We report a relatively selective full reduction of P4 at room temperature to give a unique hydrocarbon-soluble s-block metal complex of the P3ˉ anion. Key to this chemistry is a recently reported redox-active metal crown complex: (BDI*)MgNa3N″2 (VI); N″ = N(SiMe3)2 and BDI* = HC[(tBu)C═N-DIPeP]2, DIPeP = 2,6-CHEt2-phenyl. The reduction of P4 according to 2 VI + 0.25 P4 → (BDI*)MgNa5N″3P (1) + 0.5 [(BDI*)Mg]2 + 0.33 (NaN″)3 is calculated to be exothermic (ΔH = −40.5 kcal mol−1). The crystal structure of 1 shows a strongly bound (BDI*)MgP2ˉ anion with two chelating [Na-N″-Na+] and [Na-N″-Na-N″-Na+] arms of unequal length. Although these arms are highly fluxional and rapidly exchange ions, they effectively stabilize the P3ˉ anion. DFT calculations confirm the highly ionic nature of the complex and describe P3ˉ as full valence-shell anion with four lone-pairs of electrons. Reactivity studies show that the P3ˉ anion can react as a triple Brønsted base, a three-fold nucleophile or as a reducing agent.
CRIS-Team Scopus Importer:2025-09-12
Keywords: Anions; Crown; Low-valent; Magnesium; P